2006
DOI: 10.1017/s0012162206000764
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome of preterm infants with ventricular dilatation with and without associated haemorrhage

Abstract: This study investigated whether in preterm children who had ventricular dilatation (VD) on neonatal cranial ultrasound outcome at age 8 years was influenced by the additional presence of germinal matrix haemorrhage -intraventricular haemorrhage (GMH-IVH). Six-hundred and ninety-nine preterm infants (<33wks' gestation, mean 29.6wks [SD 2.1]) with either normal cranial ultrasound (n=616; 286 females, 330 males), or with VD with (n=66; 32 females, 34 males) or without (n=17; 4 females, 13 males) GMH-IVH were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 28 publications
(31 reference statements)
1
27
0
Order By: Relevance
“…2 Grade III-IV IVH and other lesions noted on ultrasound including periventricular leukomalacia (PVL), porencephaly, and ventriculomegaly are well documented to be associated with adverse neurodevelopmental outcomes. [3][4][5][6][7] However, the true impact of lower-grade IVH on the neurodevelopment of these extreme preterm infants has not been well described. IVH originates in the germinal matrix, which is the source of future neuronal and glial cells in the immature brain.…”
mentioning
confidence: 99%
“…2 Grade III-IV IVH and other lesions noted on ultrasound including periventricular leukomalacia (PVL), porencephaly, and ventriculomegaly are well documented to be associated with adverse neurodevelopmental outcomes. [3][4][5][6][7] However, the true impact of lower-grade IVH on the neurodevelopment of these extreme preterm infants has not been well described. IVH originates in the germinal matrix, which is the source of future neuronal and glial cells in the immature brain.…”
mentioning
confidence: 99%
“…This process resulted in 20 studies deemed eligible for inclusion. [14][15][16]19,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Additionally, 1 study 43 was identified and deemed eligible through searching references of included studies, bringing the final total to 21. Baseline characteristics of the 21 included studies are as shown in Supplemental Information 2.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Postmortem data shows SVZ damage in at least some infants exposed to severe hypoxia (Takizawa et al, 2006), and there is some evidence that hemorrhage in the SVZ is associated with worse neurodevelopmental outcomes (Vollmer et al, 2006). Experimentally, exposure to prolonged, severe hypoxia in preterm fetal sheep at 0.6 of gestation (equivalent to the 26-to 30-week human infant) (McIntosh et al, 1979) was associated with extensive cell death in the SVZ despite sparing of the cortex .…”
Section: The Subventricular Zone (Svz) After Hypoxic-ischemic Injurymentioning
confidence: 99%